2000
DOI: 10.1007/bf02347057
|View full text |Cite
|
Sign up to set email alerts
|

Numerical model of deep venous thrombosis detection using venous occlusion strain gauge plethysmography

Abstract: Strain gauge plethysmography (SGP) is a non-invasive method used in the detection of deep venous thrombosis (DVT). The technique is based on the measurement of calf volume changes in response to venous occlusion by a thigh cuff, the volume changes reflecting the rates of arterial inflow and venous outflow. A numerical model of the blood circulation within the limb and the response of this to a SGP test has been derived, based on treating the different parts of the circulatory system in the leg as resistance an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…Furthermore, venous compliance is reduced with advancing age , which may be one of the risk factors for varicose veins and deep vein thrombosis. Indeed, previous studies have indicated that aging induces an increase in the incidence of venous thromboembolism (Glynn et al 2007;Glynn and Rosner 2005) and that venous compliance was related to blood clot length or stenosis (Turner et al 2000). On the other hand, the intrinsic function of venous compliance is to accept blood.…”
Section: Physiological and Clinical Significancementioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, venous compliance is reduced with advancing age , which may be one of the risk factors for varicose veins and deep vein thrombosis. Indeed, previous studies have indicated that aging induces an increase in the incidence of venous thromboembolism (Glynn et al 2007;Glynn and Rosner 2005) and that venous compliance was related to blood clot length or stenosis (Turner et al 2000). On the other hand, the intrinsic function of venous compliance is to accept blood.…”
Section: Physiological and Clinical Significancementioning
confidence: 99%
“…Indeed, greater venous compliance is associated with intolerance during orthostatic stress (Olsen and Lanne 1998). In contrast, venous compliance was negatively related to venous thromboembolism, suggesting that decreased venous compliance may reflect status of venous thromboembolism, such as varicose veins and deep vein thrombosis (Turner et al 2000). Previous studies indicated that the reduction in venous compliance was preserved to a greater extent in endurance-trained men than in their sedentary peers (Hernandez and Franke 2004;Monahan et al 2001), suggesting that habitual endurance training may reduce the tolerance response to orthostatic challenge and decrease risk of venous diseases.…”
Section: Introductionmentioning
confidence: 95%
“…Some areas considered for discussion but not included in this policy were utilization of lowmolecular-weight heparin, [13][14][15][16] effectiveness of aspirin in DVT prophylaxis, 17 indications for vena cava filter placement, 18 risk factors for predicting reoccurrence, 19 computed tomography (CT) and magnetic resonance imaging (MRI) venography, [20][21][22][23] nuclear venography, [24][25][26] impedance plethysmography, [27][28][29][30] and strain gauge plethysmography. [31][32][33] This policy is also nondirective on proposed management algorithms for the evaluation and treatment of patients with suspected DVT, as well as on how to deal with conflicting test results. 34 These areas represent topics that ACEP may address in future updates of this current policy.…”
Section: E T H O D O L O G Ymentioning
confidence: 99%
“…There were several approaches for quantitative description of the mechanical interactions in heart valve motion or vascular vessel stresses [1][2][3][4][5][6]. In vivo or in vitro parameter identi cation by inverse analyses is generally performed for evaluating the mechanical stress in a limited number of series of hemodynamic data.…”
Section: Introductionmentioning
confidence: 99%